Application of a didactic sequence for the extraction of dna from kiwi pulp - Souza, Daniel Barbosa de; Silva, Vinicius Diogo da; Araujo, Débora Pereira (Brazilian Journal of Production Engineering, 2023)
A didactic sequence for removing DNA through kiwi pulp is a set of activities organized and planned to teach students, especially in high school, how to extract genetic material in a practical and engaging way. This pedagogical approach involves steps such as preparing a DNA removal solution, macerating the kiwi fruit pulp, adding the removal solution to the pulp, and observing the DNA formed at the top of the mixture after the addition of ice-cold ethanol. This teaching sequence aims to deepen students' understanding of important concepts in Genetics, such as the structure of the DNA double helix, as well as the levels of compaction of eukaryotic genetic material. Furthermore, students learn to identify and differentiate DNA from pectin, which are precipitated differently in the extraction process. This approach promotes practical and meaningful learning, encouraging students' curiosity and interest in Genetics, while developing observation, experimentation and communication skills. Practical classes, like this one, provide a more engaging and motivating experience for students, making Genetics and Chemistry content more accessible and interesting.
Keywords: Teaching following directions; Extracting DNA from kiwi fruit